Conceptual Art : and the Politics of Publicity. - Alberro, Alexander (Cambridge, Massachusetts : The MIT Press, 2003)
Siegelaub, Seth ; Graham, Dan ; Kosuth, Joseph ; Lewitt, Sol ; Weiner, Lawrence
Conceptuele kunst, rebellie tegen kunstinstituten, Artist's Right Transfer and Sale Agreement, kunst en kapitalisme
boek